RESEARCH TRENDS IN INSTRUCTIONAL TECHNOLOGY FOR SPECIAL EDUCATIONAL NEEDS: A GLOBAL BIBLIOMETRIC PERSPECTIVE - Nawi, Nur Syifaa Mohd; Hamzah, Mahizer; Rokeman, Muhammad Ihsan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
An advanced search strategy was executed, resulting in 1,261 documents for analysis. The methodology includes multiple stages: Scopus Analyser generated statistical distributions and graphical insights; OpenRefine was employed to clean, refine, and harmonise bibliographic data for precision; and VOSviewer software visualised co-authorship, keyword co-occurrence, and country collaboration networks. Hence, the results indicate an increasing trend in publications from 2015 to 2025, with significant peaks in 2022 and 2024, reflecting a growing global scholarly emphasis on technology-enhanced interventions for special needs learners. Computer Science and Social Sciences have emerged as the major disciplines, together representing more than fifty percent of total publications. The United Kingdom, the United States, Spain, and China were identified as the main contributors in terms of output and international collaboration. Keyword analysis revealed that “technology,” “special education,” “e-learning,” and “assistive technology” are central themes, with emerging clusters linked to artificial intelligence, immersive technologies, and universal design for learning. The current study helps to fill the gap in the body of knowledge, offering a thorough study of the trends in publications. Key contributors and thematic developments, thereby serving as a valuable resource for researchers, practitioners, and policymakers focused on advancing technology-driven special education needs.